Detecting conflicts of interest in credit rating changes: A distribution dynamics approach - Wai Choi Lee; Jianfu Shen; Tsun Se Cheong; Michal Wojewodzki (Financial Innovation, 2021)
In this study, we compare the adjustments of credit ratings by an investor-paid credit rating agency (CRA), represented by Egan-Jones Ratings Company, and an issuer-paid CRA, represented by Moody's Investors Service, vis-à-vis conflict of interest and reputation. A novel distribution dynamics approach is employed to compute the probability distribution and, hence, the downgrade and upgrade probabilities of a credit rating assigned by these two CRAs of different compensation systems based on the dataset of 750 U.S. issuers between 2011 and 2018, that is, after the passage of the Dodd-Frank Act. It is found that investor-paid ratings are more likely to be downgraded than issuer-paid ratings only in the lower rating grades, which is consistent with the argument that investor-paid agencies have harsher attitudes toward potentially defaulting issuers to protect their reputation. We do not find evidence that issuer-paid CRAs provide overly favorable treatments to issuers with threshold ratings, implying that reputation concerns and the Dodd-Frank regulation mitigate the conflict of interests, while issuer-paid CRAs are more concerned about providing accurate ratings.
Keywords: 650; Conflict of interest; Credit ratings; Distribution dynamics; Investor-paid credit rating agencies; Issuer-paid credit rating agencies